2015
DOI: 10.1111/cge.12616
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity in the Tunisian population

Abstract: Genetic diseases in the Tunisian population represent a real problem of public health as their spectrum encompasses more than 400 disorders. Their frequency and distribution in the country have been influenced by demographic, economic and social features especially consanguinity. In this article, we report on genetic disease association referred to as comorbidity and discuss factors influencing their expressivity. Seventy-five disease associations have been reported among Tunisian families. This comorbidity co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 51 publications
3
20
0
Order By: Relevance
“…The co‐occurrence of more than one genetic disease affecting one individual and/or different members from the same family is known as comorbidity. This phenomenon seems to be frequently reported in highly inbred populations as described by Romdhaneet al (), where 75 disease associations were reported. While Libyan population is characterized by its heterogeneous ethnic background and high rate of consanguinity (Abudejaja et al, ), the report of multiple disease associations in the same individual could be expected.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The co‐occurrence of more than one genetic disease affecting one individual and/or different members from the same family is known as comorbidity. This phenomenon seems to be frequently reported in highly inbred populations as described by Romdhaneet al (), where 75 disease associations were reported. While Libyan population is characterized by its heterogeneous ethnic background and high rate of consanguinity (Abudejaja et al, ), the report of multiple disease associations in the same individual could be expected.…”
Section: Discussionsupporting
confidence: 67%
“…While Libyan population is characterized by its heterogeneous ethnic background and high rate of consanguinity (Abudejaja et al, ), the report of multiple disease associations in the same individual could be expected. The main challenging consequence of comorbidity is undoubtedly the possibility of misdiagnosis especially when phenotypes are extremely rare and overlapping as one phenotype could be hidden by another (Romdhaneet al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Autosomal dominant disorders represent 23% of all genetic disorders reported in the country, while 5.4% are X‐linked (Romdhane & Abdelhak, ). More than one genetic condition per family, referred to as comorbidity, was also recently reported (Romdhane et al., ).…”
Section: Genetic Disorders In Tunisiamentioning
confidence: 78%
“…These marriages are practically the norm in some regions, in particular in the Southern part of the country . It has been estimated that autosomal recessive diseases risk is increased six fold as a consequence of consanguineous marriage . In addition, the co‐occurrence of two or more diseases, although rare, might be encountered in endogamous populations and is challenging for appropriate diagnosis .…”
Section: Introductionmentioning
confidence: 99%
“…It has been estimated that autosomal recessive diseases risk is increased six fold as a consequence of consanguineous marriage . In addition, the co‐occurrence of two or more diseases, although rare, might be encountered in endogamous populations and is challenging for appropriate diagnosis . Autosomal recessive congenital ichthyosis (ARCI) includes a wide range of different clinical subtypes: congenital ichthyosis form erythroderma (CIE; Online Mendelian Inheritance in Man [OMIM] 242100); lamellar ichthyosis (LI; OMIM 242300); and harlequin ichthyosis (HI; OMIM 242500) .…”
Section: Introductionmentioning
confidence: 99%